PEMELIHARAAN IKAN GABUS (Channa striata) DAN IKAN NILA (Oreochromis niloticus) DENGAN PERSENTASE PENEBARAN YANG BERBEDA PADA KOLAM TERPAL - windi adi putra; Ade Dwi Sasanti; ferdinand taqwa (Universitas Sriwijaya, 2015)
ABSTRACT Snakehead is one of fishery commodity that has a good market prospect and potential to develop as a culture fish. One of the problem in rearing of snakehead was low in survival rate. In the begining of rearing, snakehead did not respond to commercial food, because of that many culturists have not succeeded on rearing snakehead in intensive culture. Mixing of snakehead and tilapia in one pond or polyculture will affect feeding respond to commercial food. The aim of this research was to determine survival rate and growth of snakehead reared as polyculture system with tilapia due to different density percentage and similar size of snakehead and tilapia. The research held in Laboratorium Budidaya Perairan, Aquaculture Study Program, AgriculturalFaculty, Sriwijaya University in November to December 2014. The research was designed using 5 treatments and 3 replications. The treatments were P1 (100% snakehead), P2 (75% snakehead and 25% tilapia), P3 (50% snakehead and 50% tilapia), P4 (25% snakehead and 75% tilapia) and P5 (100% tilapia). The result of the research showed that different density percentage was not significantly different in survival rate and growth of snakehead. The highest survival rate of snakehead 83.3% was shown by treatment of 100% snakehead (P1). The highest survival rate among polyculture treatments was found for 75% snakehead and 25% tilapia (P2) namely 79,1%, and the lowest value 74,7% was indicated by treatment of 25% snakehead and 75% tilapia (P4). The highest absolute weight growth and absolute length growthÂ was shown by treatment of 100% snakehead (P1) namely 2,61 g and 1,9 cm, respectively the highest absolute weight growth and absolute length growth among polyculture treatments was indicated by treatment of 75% snakehead and 25% tilapia (P2), which were 2,51g and 1,8 cm, and the lowest values were 2,39 g and 1,7 cm for 25% snakehead and 75% tilapia treatment (P4). Â Key word: snakehead, tilapia, population percentage, plastic pond